EFFECT OF TAX AVOIDANCE AND PROFITABILITY ON FINANCIAL REPORTING TIMELINESS WITH OPERATIONAL COMPLEXITY AS MODERATOR - Rinaldi, Muhammad; Ariandi, Muhamad Amir; Ramadhani, Melda Aulia (STIE Pelita Nusantara Semarang, 2025)
The punctuality of financial reporting plays a crucial role for stakeholders in making well-informed and timely decisions, particularly for publicly traded companies. This research investigates the influence of tax avoidance and profitability on financial reporting timeliness, and explores whether operational complexity acts as a moderating factor in the relationship between tax avoidance and timely reporting. The study focuses on manufacturing firms within the basic and chemical industry sectors listed on the Indonesia Stock Exchange from 2021 to 2023. Employing a quantitative associative method and utilizing secondary data, the analysis was conducted through logistic regression. The findings indicate that both tax avoidance and profitability exert a significant and positive impact on financial reporting timeliness. In contrast, the complexity of a company’s operations does not significantly influence the link between tax avoidance and timely reporting.